2021
DOI: 10.1002/tal.1853
|View full text |Cite
|
Sign up to set email alerts
|

Automated topology design of high‐rise diagrid buildings by genetic algorithm optimization

Abstract: In this study, in order to determine the outer shell geometry of high-rise diagrid structures by means of minimum structural material utilization, simplified strengthand stiffness-based design methods are encoded in MATLAB with the help of SAP2000 OAPI (Open Application Programming Interface) codes and genetic algorithm (GA). The computer code is designed to get most of the inputs from the building model in SAP2000, to have minimal manual inputs that define diagrid shell geometry. The code is also built so tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In order to carry out a targeted study on the design of building electromechanical systems, seven representative energy system parameters, including energy consumption of air conditioning equipment, energy consumption of renewable energy equipment, energy consumption of cooling system, energy consumption of heating system, energy consumption of lighting, energy consumption of elevator, and building energy consumption monitoring system, were selected as the main optimization objects in this optimized design, where the target cost was determined by Chinese fixed standards combined with market prices. In order to unify the standards, the energy consumption in the above indicators is calculated by multiplying the electricity consumption during the operation period by the carbon emission factor [36], and the carbon emission factor is 0.5810 according to the latest Notice on Doing a Good Job in the Management of Greenhouse Gas Emission Reports of Enterprises in 2022 issued by the Ministry of Ecology and Environment of China. See Table 2 for specific index requirements of each parameter.…”
Section: Mathematical Model Constructionmentioning
confidence: 99%
“…In order to carry out a targeted study on the design of building electromechanical systems, seven representative energy system parameters, including energy consumption of air conditioning equipment, energy consumption of renewable energy equipment, energy consumption of cooling system, energy consumption of heating system, energy consumption of lighting, energy consumption of elevator, and building energy consumption monitoring system, were selected as the main optimization objects in this optimized design, where the target cost was determined by Chinese fixed standards combined with market prices. In order to unify the standards, the energy consumption in the above indicators is calculated by multiplying the electricity consumption during the operation period by the carbon emission factor [36], and the carbon emission factor is 0.5810 according to the latest Notice on Doing a Good Job in the Management of Greenhouse Gas Emission Reports of Enterprises in 2022 issued by the Ministry of Ecology and Environment of China. See Table 2 for specific index requirements of each parameter.…”
Section: Mathematical Model Constructionmentioning
confidence: 99%
“…It can be observed that the proposed Graph‐GEN is remarkably advantageous (an increase of 500 times), over YJK, which calculates the CMQs of each structural component after detailed structural analysis and reinforcement design. When using genetic algorithms for structural optimization, hundreds of times of CMQ estimation are typically needed (Orhan & Taşkın, 2021; X. Zhou et al., 2022). For example, a population size of 20 and an iteration number of 50 will result in 1000 possible schemes and 1000 times of CMQ estimation.…”
Section: Case Studymentioning
confidence: 99%
“…This is primarily because design optimization entails the evaluation of hundreds of potential design schemes. 3,4 If a general-purpose FE software is employed, then seismic-performance evaluation alone will consume dozens of hours, which is unacceptable in practical design scenarios when time is a critical factor.…”
Section: Introductionmentioning
confidence: 99%
“…However, the computational time for a single design scheme typically extends to several minutes or longer, which renders these software packages inadequate for satisfying design optimization demands. This is primarily because design optimization entails the evaluation of hundreds of potential design schemes 3,4 . If a general‐purpose FE software is employed, then seismic‐performance evaluation alone will consume dozens of hours, which is unacceptable in practical design scenarios when time is a critical factor.…”
Section: Introductionmentioning
confidence: 99%